Micro-Credentials and Work-Integrated Curriculum Redesign in Vocational Education: An Evidence-Informed Framework for Hospitality and Digital Business Programs - Rajesh Kumar (Kalam Practica Media, 2026)
Vocational education systems are under pressure to respond more quickly to changing skill demands while maintaining credible pathways into employment, further study, and lifelong learning. Micro-credentials have been promoted as flexible instruments for recognizing short, competency-focused learning, yet their value remains uneven when they are detached from curriculum coherence, industry validation, and authentic work-integrated assessment. This article develops an evidence-informed framework for redesigning vocational curricula through micro-credentials and work-integrated learning, with particular attention to hospitality and digital business programs. Using a conceptual framework development methodology, the study synthesizes peer-reviewed research, policy evidence, employer surveys, and work-integrated learning studies through a three-stage process: scoping, evidence mapping, and integrative framework construction. The results identify four mutually reinforcing domains: industry-aligned competency architecture, stackable credential design, workplace-integrated assessment, and learner navigation with equity safeguards. Empirical benchmark tables show that global skill transformation is accelerating, with the World Economic Forum reporting that 39 percent of key workforce skills are expected to change by 2030, while employer surveys indicate strong perceived value of micro-credentials but continuing concern about standardization and proof of effectiveness. Evidence from work-integrated learning further shows positive wage, employability, and interview effects when workplace learning is substantive rather than symbolic. The article argues that micro-credentials are most educationally valuable when they function as transparent units within a broader curriculum ecosystem, not as fragmented add-ons.